2021
DOI: 10.1051/alr/2021019
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of biofloc in carp (Cyprinus carpio var. Communis) culture as a potential tool of resource management in aquaculture

Abstract: Supplementation of biofloc in rearing of common carp (Cyprinus carpio ver. Communis (0.84 ± 0.003 g) was tested in replacing costly feed and environmental amelioration. Neem (Azadirachta indica) leave extract in biofloc media has beenknown to be beneficial in controlling pathogenic Vibrio sp. in brackish water shrimp. Two studies were conducted for 120 days in outdoor experimental cisterns with reduction of feed from 50% to 100%, with two biofloc media; without (Experiment 1; E1) and with neem extract (Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…phosphorus and nitrogenous nutrients, and, suspended solids 83 . Nitrogen, phosphorus and carbon represent the huge quantum of elements in aquaculture wastewater that are targeted for valorization 84–90 . Under minimal or zero‐water exchange and, hyper‐intensive and/or intensive culture systems, bioflocs composed of a galaxy of microorganisms, protozoa, algae, uneaten feed particles, faeces and physical debris, can be used as nutrients for selective species of fish and shrimps under reasonably controlled density 91,92 .…”
Section: Valorization Of Aquaculture Wastementioning
confidence: 99%
See 1 more Smart Citation
“…phosphorus and nitrogenous nutrients, and, suspended solids 83 . Nitrogen, phosphorus and carbon represent the huge quantum of elements in aquaculture wastewater that are targeted for valorization 84–90 . Under minimal or zero‐water exchange and, hyper‐intensive and/or intensive culture systems, bioflocs composed of a galaxy of microorganisms, protozoa, algae, uneaten feed particles, faeces and physical debris, can be used as nutrients for selective species of fish and shrimps under reasonably controlled density 91,92 .…”
Section: Valorization Of Aquaculture Wastementioning
confidence: 99%
“…Moreover, this technology imparts valuable ecological services in the process by favourably altering the heterotrophic community composition where the dominance of pathogenic Vibrio sp. is shifted towards beneficial probiotic Bacilus communities in brackish water shrimp farming earthen ponds 87–90,126 …”
Section: In Situ Circularity In Biofloc Technology (Bft)mentioning
confidence: 99%
“…The biofloc system absorbs dissolved nitrogen compounds and improves water quality . In addition, it has been demonstrated that the biofloc produced in this system may also be used to feed the shrimp and fish (Cuzon et al, 2004;Otoshi et al, 2011;Das and Mandal, 2021 a, b;Poli et al, 2021;Khanjani et al, 2022 b).…”
mentioning
confidence: 99%
“…Aquatic performance depends on many factors in the biofloc system. Biofloc production is affected by a number of biological factors including stocking density, supplemental feed and natural food availability (Xu and Pan, 2014;Zhu et al, 2016;Esparza-Leal et al, 2020;Dinda et al, 2020;Das and Mandal, 2021 a, b;Dorothy et al, 2021;Khanjani et al, 2022 b;Emerenciano et al, 2022). Similarly, abiotic factors (temperature, dissolved oxygen, salinity, total suspended solids, pH, alkalinity, light exposure, total ammonium nitrogen, nitrite and nitrate) also influence the shrimp production in BFT systems (Hostins et al, 2015;Pierri et al, 2015;.…”
mentioning
confidence: 99%
“…Similarly, Ikhwanuddin et al (2014) also found an increase in growth and survival rates of the Black tiger shrimp (Penaeus monodon) when provided with the extract of T. catappa leaves. It could be attributed to the decomposing leaf residues in the water, causing the rise in fish growth in ponds with a high N:P ratio (Das & Mandal, 2021).…”
mentioning
confidence: 99%